Two Cases of γ-Heavy Chain Disease and a Review of the Literature - I. Ramasamy; Z. Rudzki (Case Reports in Hematology)
Gamma heavy chain disease (γ-HCD) is a rare lymphoproliferative disorder characterised by the production of a truncated immunoglobulin heavy chain. Fewer than 200 cases have been reported in the literature. In some cases, γ-HCD occurs with other lymphoid neoplasms. This study reports clinical, biochemical, haematological, and histological findings in two cases of γ-HCD. We describe newer biochemical diagnostic tools (HevyLite measurement, capillary electrophoresis, and immunotyping) that can aid in the characterisation of γ-HCD. The first case is an 88-year-old woman with γ-HCD. The second case is an 81-year-old woman who developed γ-HCD during treatment for Waldenstrom’s macroglobulinemia. In the second patient, histopathology identified a separate clone responsible for the secretion of the gamma heavy chain. Studies on the clonal evolution of the disease may provide insight into therapeutic implications and the genomic complexity of the disease.